E.S. v. Austria (Eur. Ct. H.R.). (June 2019) - Smet, Stijn
Abstract : In E.S. v. Austria, the European Court of Human Rights ruled that a criminal conviction for making disparaging comments about the Prophet Muhammad, intimating in particular that he was a pedophile, did not violate the speaker's right to freedom of expression under Article 10 of the European Convention on Human Rights (ECHR).